Rekonstruksi Peran Indonesia sebagai Negara Berkembang melalui Intervensi Yuridis terhadap Base Erosion and Profit Shifting (BEPS) - Solihan Makruf; Rizal Agung Mufti; Muhammad Abdi Dermawan; Asep Husni; Nandang Najmudin (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2026)
This study aims to reconstruct Indonesia’s role as a developing country in addressing the practice of Base Erosion and Profit Shifting (BEPS) through strategic and responsive juridical interventions. The research contributes to enriching academic discourse and provides relevant legal policy recommendations to strengthen the national taxation system against cross-border tax avoidance. The methodology employed is a normative juridical approach with a descriptive-analytical method, conducted through library research on national regulations and international legal instruments, such as the OECD BEPS Action Plan. The findings indicate that although Indonesia has adopted several BEPS actions, there remain gaps in regulatory harmonization and institutional capacity that need to be reconstructed to enable Indonesia to play a more significant role in the global tax order.